E-tendering adoption in the Malaysian construction industry: contractors’ perspectives on benefits, challenges and solutions - Ali, Suhaila; Jenuwa1, Norsyazwana; Md Dahlan, Farhan; Abu Bakar, Norbaizura; Md Zain, Noraini (Universiti Teknologi MARA, Sabah, 2025)
The conventional paper-based tendering method commonly used by contractors in the Malaysian construction industry has several shortcomings, such as limited transparency and excessive bureaucratic procedures. Despite these flaws, it remains the standard approach for project bidding. To address these inefficiencies, the government introduced the E-Tender system in 2008 as part of the Government Application initiative. This initiative aims to replace the manual tendering practices in public agencies with a more systematic Internet-based procurement platform. However, similar to any transition project, the shift to e-tendering in the Malaysian construction sector has encountered various challenges. This study aims to identify both the advantages and challenges faced by contractors when implementing the e-tendering system and to suggest potential solutions to overcome these challenges. The research is based on a survey involving 144 respondents, who evaluated and ranked the challenges according to their significance. The findings reveal that the top three benefits of adopting e-tendering are lower costs in procurement, reduced service expenses, and overall cost savings. On the other hand, the most significant challenge identified is the high initial implementation cost. To address this, the study recommends ensuring a user-friendly interface, system usability, compatibility with low-speed Internet connections, and strong support from top management as effective solutions.